If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3y + -5) + -5y = -9 Reorder the terms: 2(-5 + 3y) + -5y = -9 (-5 * 2 + 3y * 2) + -5y = -9 (-10 + 6y) + -5y = -9 Combine like terms: 6y + -5y = 1y -10 + 1y = -9 Solving -10 + 1y = -9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 1y = -9 + 10 Combine like terms: -10 + 10 = 0 0 + 1y = -9 + 10 1y = -9 + 10 Combine like terms: -9 + 10 = 1 1y = 1 Divide each side by '1'. y = 1 Simplifying y = 1
| -4(2.5s-5.5)=-19.5-7s | | 4x+6+3=27 | | 4+d=-12 | | 6k-32=-2k | | -3(4y+4)-10=-8(y+4)+4y | | 90-(8x-20)+y= | | x^2-8=-2s | | 5x+6=-22 | | 6x+22=13x-6 | | 2(5y+7)+6+3y=30 | | -17.5-4.5a=8(3.5a-5) | | (x-13)=2 | | 10+50=8x+60 | | 16f-3=16f-8 | | 9X-2(-8)=7(X+1)+6 | | b^2+b-30=30 | | (n-4)=13 | | 7(4.5-6b)=25.5 | | 5a+12=2a-20 | | 3(25+x)=275 | | X+55=120+15 | | (8x-20)+y=90 | | -5+6m=25 | | 9.5f-5f=23.5 | | 5(2-4x)=250 | | 4s-63=5s | | 4(3x-5)+6=4x-14+8x | | -7x-7=-x-67 | | -20.5=-8.5+3.5(y+9) | | t=-0.5+15x-1 | | 22.5=-3(8.5d+5) | | -9.5(6v+6.5)=-22.5 |